Social inquiry after Wittgenstein & Kuhn : leaving everything as it is - Gunnell, John G. (EBL-Schweitzer, 2014)
John G. Gunnell argues that a distinctive feature of Ludwig Wittgenstein's work after 1930 was his turn to a conception of philosophy as a form of social inquiry and that Thomas Kuhn's approach to the philosophy of science exemplified this conception. He further contends that their work addresses foundational issues in the social and human sciences and particularly the vision of social inquiry as an interpretive endeavor, as well as the distinctive cognitive and practical relationship between social inquiry and its subject matter. Gunnell speaks directly to philosophers and practitioners of t.